A 3D FEM Study on the Axial Compressive Behavior of Normal Concrete Composite Square Columns with UHPC Internal Core - Nguyen, Thanh Vy; Nguyen, Tuan Anh; Le, An Hoang (Engineering, Technology & Applied Science Research, 2025)
This study uses the ABAQUS platform to develop a three-dimensional Finite Element Model (3D FEM) and analyze the axial compressive behavior of square composite columns consisting of Normal-Strength Concrete (NSC) with embedded Ultra-High-Performance Concrete (UHPC) cores. This study uses a complete 3D modeling approach that considers key parameters, such as the core shape, number of cores, and steel fiber content within the UHPC, in contrast to most existing research, which focuses on experimental studies on two-dimensional simulations. The simulation results strongly agree with the experimental data regarding the crack patterns, compressive strength, and deformation behavior. Additionally, a parametric analysis was conducted in ABAQUS to examine how UHPC core strength and thickness influence the structural performance. This approach offers a practical and efficient solution for assessing structures where experimental data are limited—a common issue in the existing literature.